The Military History of the Korean War - Marshall, S. L. A. (Samuel Lyman Atwood), 1900-1977 (New York Franklin Watts Inc., 1972)
Military action including the desperate air war in "MIG Alley", the back-and-forth struggle for the 38th parallel, and the truce. Grades 7-10.
Includes Index and Illustrations.
Keywords: Korean War (1950-1953)